Aesthetics of scenography in children's theater performances (A play waiting for birds as a model ( (Texas Journal of Philology, Culture and History, 2023)
There is no doubt that each of the arts has a material from which the aesthetic achievement is built, so the researcher found that there are aesthetics for the scenography of children's theater performances that establish a creative artistic achievement, as the research deals with the artistic and aesthetic values of the scenography in children's theater performances, which consists of a group of elements that provoke aesthetic emotion in the recipient (The child) by organizing and attracting these elements so that each of them takes its correct position in order to fully perform its formal, aesthetic and artistic function, so that the meaning and the element of beauty are achieved for the recipient and make him an effective element in the theatrical show. Therefore, the researcher proceeded to study these aesthetics in the scenography of children's theater performances and divided them into four chapters. It is also of cognitive importance as it provides an objective study for researchers in theatrical sciences at the technical and directive level, as well as the research objective (knowing the aesthetics of scenography in children's theater performances). (The concept of beauty) from the standpoint of the general and its employment in theater scenography in particular, and the second topic (the foundations of scenography in children's theater) and how these aesthetic technical foundations were associated with theatrical performance, as for the third topic, (sources of scenography for children's theater) and the chapter concluded with what resulted in the theoretical framework, And then the third chapter, which included the procedures and analysis of the sample form, and finally the fourth chapter, which included the results and conclusions, and then the references